PERILAKU MORAL HAZARD NASABAH PADA PEMBIAYAAN BERBASIS BAGI HASIL PADA PERBANKAN SYARIAH - Asmirawati Asmirawati; Sumarlin Sumarlin (LAA MAISYIR: Jurnal Ekonomi Islam, 2018)
Moral hazard of the client becomes one of the factors causing the low implementation of profit-sharing financing that is mudharabah and musyarakah. This research uses qualitative research paradigm with research location at PT Bank BNI Syariah Makassar Branch. Researchers take data with interview techniques and some other secondary data support from the official website of the entity. Then the researchers analyze the data and interpret the data obtained. The results showed that the moral hazard behavior of customers in PT BNI syariah Makassar branch is one of the risks that must be borne by the bank related to profit-sharing financing, because this financing is primarily Mudharabah is Character based financing or in distribution not only see the guarantee provided by the customer but will see the character of the customer. Moral hazard actions conducted by the customer is to cheat in terms of collateral, mark-up the cost of work load in musyarakah financing and not make payment in accordance with the aqad.